High-Volume Peritoneal Dialysis in Acute Kidney Injury: Indications and Limitations - Ponce, Daniela [UNESP]; Berbel, Marina Nogueira [UNESP]; de Goes, Cassiana Regina [UNESP]; Puato Almeida, Cibele Tais [UNESP]; Balbi, André Luis [UNESP] (Amer Soc Nephrology, 2012)
Background and objectives Peritoneal dialysis is still used for AKI in developing countries despite concerns about its limitations. The objective of this study was to explore the role of high-volume peritoneal dialysis in AM patients in relation to metabolic and fluid control, outcome, and risk factors associated with death.Design, setting, participants, & measurements A prospective study was performed on 204 AKI patients who were assigned to high-volume peritoneal dialysis (prescribed Kt/V=0.60/session) by flexible catheter and cycler; 150 patients (80.2%) were included in the final analysis.Results Mean age was 63.8 +/- 15.8 years, 70% of patients were in the intensive care unit, and sepsis was the main etiology of AKI (54.7%). BUN and creatinine levels stabilized after four sessions at around 50 and 4 mg/dl, respectively. Fluid removal and nitrogen balance increased progressively and stabilized around 1200 ml and -1 g/d after four sessions, respectively. Weekly delivered Kt/V was 3.5 +/- 0.68. Regarding AKI outcome, 23% of patients presented renal function recovery, 6.6% of patients remained on dialysis after 30 days, and 57.3% of patients died. Age and sepsis were identified as risk factors for death. In urine output, increase of 1 g in nitrogen balance and increase of 500 ml in ultrafiltration after three sessions were identified as protective factors.Conclusions High-volume peritoneal dialysis is effective for a selected AKI patient group, allowing adequate metabolic and fluid control. Age, sepsis, and urine output as well as nitrogen balance and ultrafiltration after three high-volume peritoneal dialysis sessions were associated significantly with death. Clin J Am Soc Nephrol 7: 887-894, 2012. doi: 10.2215/CJN.11131111